2013
DOI: 10.1007/978-1-62703-441-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclic Nucleotide Gated Channels Using Regular Expressions

Abstract: Cyclic nucleotide-gated channels (CNGCs) are nonselective cation channels found in plants, animals, and some bacteria. They have a six-transmembrane/one-pore structure, a cytosolic cyclic nucleotide-binding domain, and a cytosolic calmodulin-binding domain. Despite their functional similarities, the plant CNGC family members appear to have different conserved amino acid motifs within corresponding functional domains than animal and bacterial CNGCs do. Here we describe the development and application of methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…in maize plant CNGCs and does not occur in the ion transporters found in other plants, such as rice, Arabidopsis, and tomato (Saand et al 2015b;Nawaz et al 2014;Zelman et al 2013). In this study, 12 ZmCNGCs were identified and the PBCs and hinge domains were highly conserved after alignment, which further confirmed the previous hypothesis (Saand et al 2015b) Manuscript to be reviewed 2013).…”
Section: Features and Evolution Of Plant Cngc Family Genessupporting
confidence: 86%
See 2 more Smart Citations
“…in maize plant CNGCs and does not occur in the ion transporters found in other plants, such as rice, Arabidopsis, and tomato (Saand et al 2015b;Nawaz et al 2014;Zelman et al 2013). In this study, 12 ZmCNGCs were identified and the PBCs and hinge domains were highly conserved after alignment, which further confirmed the previous hypothesis (Saand et al 2015b) Manuscript to be reviewed 2013).…”
Section: Features and Evolution Of Plant Cngc Family Genessupporting
confidence: 86%
“…[FYL]-X- [LIVF], in the PBC and hinge region within the CNBD of CNGC proteins only exists in plant CNGCs and does not occur in other ion transporters (Zelman et al 2013;Saand et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual plant CNGC genes were identified in several plant species including barley ( Schuurink et al, 1998 ), Arabidopsis ( Kohler et al, 1999 ; Kohler and Neuhaus, 2000 ) and tobacco ( Arazi et al, 1999 ). Genome-wide identification of CNGC gene family was also conducted in Arabidopsis ( Maser et al, 2001 ), rice ( Bridges et al, 2005 ), Populus trichocarpa ( Ward et al, 2009 ), pear ( Chen et al, 2015 ), a moss ( Physcomitrella patens ) and some algae ( Verret et al, 2010 ; Zelman et al, 2013 ). The Arabidopsis CNGC gene family is comprised of 20 members that are divided into groups I, II, III, IVa, and IVb according to their phylogenetic relationship ( Maser et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a plant CNGC-specific motif spanning the phosphate binding cassette (PBC) and hinge region within CNB domain of CNGC proteins is predicted. This motif identifies CNGCs but no other protein and thus represents an efficient tool to identify plant CNGCs, which has been validated in several species such as Arabidopsis , rice, P. patens and Selaginella moellendorffii ( Zelman et al, 2012 , 2013 ). Based on animal research, it has been suggested that plant CNGCs might conduct calcium.…”
Section: Introductionmentioning
confidence: 99%